Enhancing Pre-service Physics Teachers' Higher-Order Thinking Skills Through STEM-PjBL Model - Haryadi, Rudi; Pujiastuti, Heni (International Journal of STEM Education for Sustainability, 2022)
This study aimed to determine the higher-order thinking skills of pre-service teachers through STEM-PjBL Model. The research method used was a quasi-experimental with one group pretest-posttest design. The N-Gain results mention the N-gain in both experimental and control classes that the physics learning process through the STEM-PjBL Model is 21% higher in improving higher-order thinking skills than Direct Learning. Improvement of students' ability to solve HOTS categorical questions in the experimental group taught by applying STEM-PjBL Model scored N-Gain 75% or 0.75, which increases the high category. In comparison, the control group led by applying the Direct Learning model achieved 54% or 0.54, meaning a moderate increase in categories. The results showed that learning using STEM-PjBL Model could improve higher-order thinking skills more than Direct Instruction Learning. The implications of this research include: gaining new knowledge that can be used as a pre-service teacher’, adding insight regarding STEM-PjBL Model that can be used to grow students' science process skills, assisting schools in improving the quality of students, and the quality of the physics learning process in schools.